Expectations of the end: a comparative traditio-historical study of eschatological, apocalyptic, and messianic ideas in the Dead Sea scrolls and the New Testament - Hogeterp, Albert L. A. (Studies on the texts of the desert of Judah 0169-9962, 2010)
Toward comparative study of eschatological ideas in Qumran and in emerging Christianity -- Integrating Qumran eschatology into late Second Temple Judaism -- Emerging Christianity and eschatology -- Resurrection of the dead in the Dead Sea scrolls and the New Testament -- Apocalypticism in Qumran and the New Testament -- Messianism in Qumran and the New Testament